A study of linguistic features of chairman messages in bankannual reports in English versus Vietnamese - Võ, Thị Ngọc Diễm. (The University of Da Nang, 2014)
An annual report is part of every established organization document. In Vietnam, it is indispensable for any public companies listed on the country’s stock market. This thesis is a study of linguistics features of Chairman Messages in bank annual reports in English versus Vietnamese. The data used in observation and analysis are taken from 100 chairman messages in both languages. Through this study, a qualitative analysis and a descriptive approach have been done to explain some concepts involved in the syntactic features, lexical features and cohesive devices used in Chairman Messages in English versus Vietnamese. Moreover, the data analysis showed the similarities and differences of these features between two languages and put forward some implication for English language teaching and learning, for learners as well as anyone who are interested in English and Vietnamese Chairman Messages. Hopefully, the study will bring practical benefits to compile a formal chairman message.